DAMPAK PENAMBANGAN BATU GAMPING TERHADAP CADANGAN AIR TANAH (Studi Kasus : Penambangan Batu Gamping, Maruni, Manokwari, Papua Barat): THE IMPACT OF LIMESTONE MINING ON GROUNDWATER RESERVES (Case Study : Limestone Mining, Maruni, Manokwari, West Papua) - Khristian Enggar Pamuji (JISTECH: Journal of Information Science and Technology, 2014)
This research has been conducted in the limestone mining areal, Maruni, South Manokwari district, Manokwari regency, West Papua province. The purpose of this research was to analyze the impact of the limestone mining to groundwater reserve, using APLIS methode. The variables used in this study were altitude (elevation) above sea level, slope, lithology, infiltration zone, and soil.The result of this research shows that groundwater reserve has decreased. Limestone mining activities will reduce groundwater reserve up to 72%.